Landcover analysis on cultural landscape along the Kuala Selangor – Sabak Bernam rural tourism route - Ibrahim, Illyani; Zakariya, Khalilah (2019)
This research considers the use of earth observation sensors to map the land cover that shapes the cultural landscape along a rural tourism route. The aim of this research is to study the landscape features that can be seen by the tourists from Kuala Selangor to Sabak Bernam, located in the state of Selangor, Malaysia. The objectives of the study are twofold: (i) to prepare a map of land cover types along the rural route and (ii) to prepare a map of the cultural landscape and the land cover. The method employed for this study was by using Supervised Classification that requires the training data to classify appropriate spectral signatures. The findings show that 80% of the landscape features along the Points of Interest (POI) are paddy fields. The presence of the paddy fields along the route represents the dominant agricultural activities of the locals living in the area, particularly in the area of Sekinchan. The changing seasons of the paddy fields mark the cycle of agricultural activities by the locals, while at the same time providing a scenic view of the rural landscape. The geographic character of the area, which was predominantly flat land, made it suitable for agricultural activities to be done. Hence, paddy farming became a way of life and consequently forms the cultural landscape of the place. According to the analysis on mapping of the POI, the route has potentials to be a tourism route based on the presence of natural attractions, rural settlements, heritage and local food, alongside the visual scenery of the paddy fields. This research concludes that land cover types can determine the activities of a place that represents the cultural landscape.